Pesticide Residues Monitoring of Organophosphorus and Carbamates in Grapes in Three Egyptian Governorates - Ali M. Shams El Din; Mohamed M. Azab; Mohamed A. Shalaby (Archives of Current Research International, 2018)
To assess the level of pesticide residues of 21 organophosphorus (OPs) and 5 carbamates (Carbs) in grapes, a total number of 96 samples of grape fruits and leaves was purchased from the markets of Qalyubia, Sharkia and Minufiya governorates during 2012 and 2013. The multi-residue extraction, QuEChERS (quick natural cheap effective rugged and safe) was used for the pesticide residues. Gas chromatography coupled with FPD detector (GC- FPD) and high-performance liquid chromatography with a photodiode array detector (HPLC -PDA) was used for the determination of pesticides residues. Results revealed that all detected pesticide residues in fruit or leaves samples were above the accepted maximum residue limit (MRL). Oxamyl and profenofos were the most detected in fruit samples, 22.92% followed by carbofuran and triazophos (20.83% of samples each). In leaves, oxamyl was the most detected in 47.92% of samples followed by chlorpyrifos in 45.83% of samples. An increase in pesticides contaminated samples analysed in 2013 than in 2012 was observed. Furthermore, the samples of Qalyubia were the highest contaminated followed by the samples of Sharkia then Minufiya during the two investigated years.